Large‐Vessel Occlusion Stroke Knowledge and Training for Stroke Severity Assessment Among Emergency Medical Services Personnel in the United States - Kaiz S. Asif; Robin Novakovic; Thanh N. Nguyen; Santiago Ortega‐Gutierrez; Youngran Kim; Amanda Jagolino‐Cole; Sushanth Aroor; Alicia Castonguay; Prateek Kumar; Ashutosh P. Jhadav; Dileep Yavagal; May Nour; et al. (Stroke: Vascular and Interventional Neurology)
Background Prehospital identification of large‐vessel occlusion (LVO) stroke facilitates the development of a regional triage protocol that could lead to an improvement in intrahospital and interhospital workflows. This requires stroke education of emergency medical services (EMS) personnel to improve stroke recognition, severity assessment, and prenotification. However, the current state of EMS personnel's knowledge of LVO stroke, their training for stroke severity assessment, and their preferences for educational methods are unknown. We conducted a nationwide EMS survey across the United States to glean insights that can inform and customize future EMS educational efforts. Methods The Society of Vascular and Interventional Neurology, in collaboration with EMS World, created an online questionnaire for EMS personnel. It included 12 multiple‐choice and free‐response questions designed to test participants’ clinical knowledge of LVO, knowledge of stroke center certification levels, prior LVO educational experiences, preferences for educational content delivery, and perspectives on prehospital hurdles to stroke care. All subscribers of EMS World received a survey link via email. Results Of the 38 486 subscribers of EMS World, the survey email was opened by 1830, of whom 1107 completed the survey across all states in the United States, with a response rate of 2.9%. Most of the respondents identified themselves as paramedics/emergency medical technicians (91%). The number of patients with stroke that survey participants transported in the past year was <10 for 618 (56%). Only 285 (26%) participants answered both LVO knowledge questions correctly, and only 128 (12%) respondents correctly identified all types of stroke centers with thrombectomy capability. A total of 362 EMS personnel (33%) denied receiving training to perform LVO severity assessment. Respondents who received training to perform an LVO scale demonstrated nearly twice the prevalence of LVO knowledge (30.6% versus 15.7%; prevalence ratio, 1.94 [95% CI, 1.50–2.53]) than respondents who did not receive training. The top hurdle to prehospital LVO education was identified as the lack of standardized LVO training by 535 (48%) respondents. Conclusions EMS providers in the United States reported inadequate LVO training and demonstrated gaps in knowledge of LVO, stroke severity scales, and stroke center levels. Systematic efforts to enhance and standardize the educational content and delivery of LVO education are needed.